INTENSITY OF THE METHODOLOGICAL APPROACH IN TEACHING LANGUAGE GRAMMAR - Mamadaliyeva F.A (Western European Studies, 2024)
Language is a system that operates on the basis of complex mechanisms, refined throughout the history of the language. Intensive methods are built on the basis of the global presentation of language material, formalized in structures or models. The development of grammatical mechanisms is provided from the dialogues of the main course - based on models. The goal of teaching foreign languages is practical knowledge of spoken language and professional speech.
Keywords: method; speech; language; model transformation